The Relationship of Teacher Competence to the Performance of Elementary School Physical Education Teachers - Priadi Nasrulloh; Ayi Suherman; Dewi Susilawati (JUARA : Jurnal Olahraga, 2022)
The teacher is a powerful component in educational success. One of the supporting factors for teacher quality is teacher performance. This study aims to analyze the relationship of teacher competence to the implementation of public elementary school teachers in Bandung Regency. The population and samples in this study were all public elementary school corner teachers in Baleendah District, Bandung Regency, who sold 53 people. This research is a quantitative study using a descriptive correlation analysis method. Research results in data processing and analysis show that pedagogic competence, professional competence and social competence both partially and simultaneously affect teacher performance with positive and significant results.